Pengaruh Kegiatan Bercocok Tanam Sayuran Terhadap Literasi Sains Anak Usia 5-6 Tahun di TK Santo Thomas 2 Kota Medan - Purba, Alyeska Azrina; Handayani, Peny Husna (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2024)
The problem in this research lies in the lack of stimulation of early childhood science literacy skills in science learning at Santo Thomas 2 Kindergarten, Medan City. In fact, one of the things that needs to be achieved from an early age is scientific literacy, seen from the elements in the independent curriculum. The aim of this research was to determine the effect of vegetable planting activities on the scientific literacy of children aged 5-6 years at Santo Thomas 2 Kindergarten, Medan City. The sample that the researchers used was 20 children in class B Ceria. The type of research used is quantitative experimental with a pre-experimental research design. The research results showed that there was an increase in the average score of the pre-test score of 19 and the post-test score of 32. This data shows that vegetable farming activities have an influence on the scientific literacy of class B Ceria children aged 5-6 years at Santo Kindergarten. Thomas 2 Medan City, with SPSS results, the value of Asymp, Sig (0.000) is smaller than the value of α (0.05)